Molecular Paleoclimate Reconstructions over the Last 9 ka from a Peat Sequence in South China - Wang, Xinxin; Huang, Xianyu; Sachse, Dirk; Ding, Weihua; Xue, Jiantao (PLOS ONE, 2016)
To achieve a better understanding of Holocene climate change in the monsoon regions of China, we investigated the molecular distributions and carbon and hydrogen isotope compositions (δ13C and δD values) of long-chain n-alkanes in a peat core from the Shiwangutian (SWGT) peatland, south China over the last 9 ka. By comparisons with other climate records, we found that the δ13C values of the long-chain n-alkanes can be a proxy for humidity, while the δD values of the long-chain n-alkanes primarily recorded the moisture source δD signal during 9–1.8 ka BP and responded to the dry climate during 1.8–0.3 ka BP. Together with the average chain length (ACL) and the carbon preference index (CPI) data, the climate evolution over last 9 ka in the SWGT peatland can be divided into three stages. During the first stage (9–5 ka BP), the δ13C values were depleted and CPI and Paq values were low, while ACL values were high. They reveal a period of warm and wet climate, which is regarded as the Holocene optimum. The second stage (5–1.8 ka BP) witnessed a shift to relatively cool and dry climate, as indicated by the more positive δ13C values and lower ACL values. During the third stage (1.8–0.3 ka BP), the δ13C, δD, CPI and Paq values showed marked increase and ACL values varied greatly, implying an abrupt change to cold and dry conditions. This climate pattern corresponds to the broad decline in Asian monsoon intensity through the latter part of the Holocene. Our results do not support a later Holocene optimum in south China as suggested by previous studies.